a critical history - "May, Christopher"; "Sell, Susan K" (New Delhi, 2008)
Why you need to know about intellectual property -- Ideas and technology -- The emergence of intellectual property rights -- Commerce vs. romantic notions of authorship and invention -- The nineteenth century : technological development and international law -- The twentieth century : intellectual property rights consolidated -- The twenty-first century : TRIPS and beyond -- Forgetting history is not an option
includes bibliography and index
Keywords: Intellectual property--History; Intellectual property--Political aspects; Intellectual property--Social aspects